FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BERAT BADAN BALITA BAWAH GARIS MERAH (BGM) DI WILAYAH KERJA PUSKESMAS SELINDUNG KOTA PANGKALPINANG (JURNAL SMART ANKES, 2021)
Below red line Infants are the infants which weights are below the red line on the Health Check Card (KMS). The data from the Health Department of Pangkalpinang Municipality show the case of BGM infants in 2016 were 61 cases, in 2017 the cases increased to 92 cases, and in 2018 the case of BGM infants decreased to 61 cases. This study aims to know the related factors towards the occurrence of below red line (BGM) weight on infants in the work area of Public Health Center Selindung. This research employs a case control research design. The population of this research is the entire infants in the work area of Public Health Center Selindung with the total number of 2.001 infants. From the population, the case samples are 11 infants, and the control samples are 33 infants. The dependent variable of this study is BGM infants, and the independent variables are mothers’ education, mothers’ knowledge, mothers’ occupation, family earnings, health care facilities, and medical officers’ role. The rate of case sample and control sample is set at 1 : 3. The case samples are 11 infants, and the control samples are 33 infants, so the total number of samples are 44 infants. The sample are dawn using drawn Systematic Random Sampling Technique. The data are analyzed using Chi-square test. The result of this reseach show that there are significant relations between variables of mothers’ education with score ​​(p=0,005 OR=12,000), mothers’ knowledge (p=0,027 OR=6,720), family earnings (p=0,000 OR=85,333) and health care facilities (p=0,024 OR=8,333) with the occurrence of below red line (BGM) weight on infants in the work area of Public Health Center Selindung. Whereas, there is no significants relation between the variable of mothers’ occupation ​​(p=0.486), and medical officers’ role (p=0,592), with the occurrence of below red line (BGM) weight on infants in the work area of Public Health Center Selindung